Community Partnerships Based on Responsive Law as Preservation Strategies in The Dieng Temple Complex - Aziz Zaelani, Muhammad; Dewi, Nourma (Alauddin Law Development Journal, 2024)
This study addresses the challenges of community partnerships in the conservation of zoning and cultural heritage in the Dieng Temple complex. Using a sociological legal research method, it aims to formulate a partnership model to optimize conservation strategies. The preservation of cultural heritage objects has been marginalized due to factors such as the lack of community involvement, which has not been accommodated by the Cultural Preservation Center of Region X. Synergy with the Banjarnegara Regency Government and the Dieng community is essential. The results show that uncontrolled mass tourism, regulatory issues, and environmental degradation hinder preservation efforts. The proposed partnership model involves community participation, the establishment of a Dieng Temple Area Conservation Information Center, and optimizing the role of the Banjarnegara Tourism Office.